Total intracorporeal robotic renal auto-transplantation: A new minimally invasive approach to preserve the kidney after major ureteral injuries. (2018) - Doumerc, Nicolas; Beauval, Jean-Baptiste; Roumiguié, Mathieu; Roulette, Pauline; Laclergerie, Florian; Sallusto, Federico; Soulié, Michel; Gamé, Xavier; Biscans, Clément
Highlights: RATx is a suitable option for managing patients with major ureteric injury. The procedure was performed via a transperitoneal approach, with the robotic assistance. The kidney was perfused intracorporealy with a ice-cold Ringer solution. This is the first case successfully performed as a total robotic approach outside of North America. Abstract: Background: Renal auto-transplantation is a suitable option for managing patients with major ureteric injury. Conventional Renal auto-transplantation is however, underutilized because of its invasiveness. Completely intra-corporeal robotic renal auto-transplantation is a suitable option to decrease the morbidity. In this case, we report the first use of total intra-corporeal robotic renal auto-transplantation outside of North America. Case report: A 30-year-old woman presented with an extensive upper left ureter defect, following a high kinetic energy trauma. She underwent 2 median laparotomies, with extensive resection of small intestine, and 1 transverse laparotomy to repair a massive rupture of abdominal muscles. The procedure was performed via a transperitoneal approach, with the assistance of the da Vinci Si robot (Intuitive Surgical Inc. Sunnyvale, CA, USA). The renal auto-transplantation was conducted entirely robotically, in 2 separate stages, using a 4 robotic arm approach. Total operative time was 300 min: 150 min to harvest the kidney including adhesiolysis, 20 min to reposition the patient, and 130 min for the robot assisted kidney transplantation (RAKT). The total ischemia time was 96 min (3 min of warm ischemia, no cold ischemia, 93 min of rewarming time). The estimated blood loss was 150 mL. Conclusion: To our knowledge, this is the first case successfully performed as a total robotic approach outside of North America.